PENGARUH PEMBERIAN EKSTRAK DAUN KEMANGI (OCIMUM SANCTUM) TERHADAP PENURUNAN KOLESTEROL TOTAL TIKUS PUTIH (RATTUS NORVEGICUS STRAIN WISTAR) YANG DIINDUKSI MONOSODIUM GLUTAMATE (MSG). - Brain Gantoro; Yani Christina; Emylianti Aidah Putri (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2025)
ABSTRACT Background: Hypercholesterolemia is a condition where cholesterol levels increase above normal limits. Flavonoids found in plants functioning as natural antioxidants with their ability to ward off free radical molecules. One of these plants is basil leaves (Ocimum sanctum). The aim of this research was to determine the effect of basil leaf extract on reducing cholesterol levels in mice. Methods: This study used a true experimental design in vivo in the laboratory with Post test Only Control Group design and a total sample of 35 experimental animals grouped into 5 groups, namely the negative control group only given standard feed, the positive control group given MSG 0.2 g / kgBB for 14 days, and the treatment group consisting of 3 groups induced by MSG for 14 days and basil leaf extract at a dose of 175 mg/kgBB, 350 mg/kgBB, 700 mg/kgBB for 10 days. Analysis of the results using One Way Anova test followed by Post Hoc LSD analysis to see differences between groups. Results: Ocimum sanctum extract was able to reduce total cholesterol levels in mice induced by MSG with a significance of p = 0.000. Conclusion: The most effective reduction in total cholesterol levels was at a dose of 700 mg/kgBB Keywords: Basil leaf, Cholesterol, Hypercholesterolemia